(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The main objective of this study is to address the procrastination encountered by grade 12 Senior High School Humanities and Social Science Students. From the result of this study, according to our research, almost half of eight sections are experiencing procrastination, ages between 17 and 19. Moreover, this study recommended that even if they encounter procrastination, students must handle it properly for them to do their tasks. Also, being responsible for prioritizing tasks and having time management is essential and makes them more productive and set goals to ease their task.